2016
DOI: 10.2967/jnumed.116.176313
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting Pathologic Response of Esophageal Cancer to Neoadjuvant Chemotherapy: The Implications of Metabolic Nodal Response for Personalized Therapy

Abstract: Only a minority of esophageal cancers demonstrates a pathologic tumor response (pTR) to neoadjuvant chemotherapy (NAC). 18 F-FDG PET/CT is often used for restaging after NAC and to assess response. Increasingly, it is used during therapy to identify unresponsive tumors and predict pTR, using avidity of the primary tumor alone. However, definitions of such metabolic tumor response (mTR) vary. We aimed to comprehensively reevaluate metabolic response assessment using accepted parameters, as well as novel concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…mNR comprised: complete metabolic response (CMR); partial metabolic response (PMR; reduction in mN category or SUVmax by at least 30 per cent); stable metabolic disease (SMD; stable mN category or reduction/progression in SUVmax below 30 per cent); or progressive metabolic disease (PMD; progression of mN category or SUVmax by at least 30 per cent). Optimal metrics of mTR for predicting pTR were as described previously, using receiver operating characteristics (ROCs). In brief, these comprised: SUVmax −77·8 per cent, avid length −57·8 per cent, PET Response Criteria in Solid Tumors (PERCIST) –30 per cent, Metabolic response evalUatioN for Individualization of neoadjuvant Chemotherapy in oesOphageal and oesophagogastric adeNocarcinoma (MUNICON) –35 per cent, mean SUV (SUVmean) –36·8 per cent, peak SUV (SUVpeak) –69·8 per cent, metabolic tumour volume (MTV) –89·6 per cent, maximum tumour glycolytic volume (TGV) –93·8 per cent, mean TGV –89·2 per cent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…mNR comprised: complete metabolic response (CMR); partial metabolic response (PMR; reduction in mN category or SUVmax by at least 30 per cent); stable metabolic disease (SMD; stable mN category or reduction/progression in SUVmax below 30 per cent); or progressive metabolic disease (PMD; progression of mN category or SUVmax by at least 30 per cent). Optimal metrics of mTR for predicting pTR were as described previously, using receiver operating characteristics (ROCs). In brief, these comprised: SUVmax −77·8 per cent, avid length −57·8 per cent, PET Response Criteria in Solid Tumors (PERCIST) –30 per cent, Metabolic response evalUatioN for Individualization of neoadjuvant Chemotherapy in oesOphageal and oesophagogastric adeNocarcinoma (MUNICON) –35 per cent, mean SUV (SUVmean) –36·8 per cent, peak SUV (SUVpeak) –69·8 per cent, metabolic tumour volume (MTV) –89·6 per cent, maximum tumour glycolytic volume (TGV) –93·8 per cent, mean TGV –89·2 per cent.…”
Section: Methodsmentioning
confidence: 99%
“…mNR comprised: complete metabolic response (CMR); partial metabolic response (PMR; reduction in mN category or SUVmax by at least 30 per cent); stable metabolic disease (SMD; stable mN category or reduction/progression in SUVmax below 30 per cent); or progressive metabolic disease (PMD; progression of mN category or SUVmax by at least 30 per cent). Optimal metrics of mTR for predicting pTR were as described previously, using receiver operating characteristics (ROCs) 20…”
Section: Pet-ct Variablesmentioning
confidence: 99%
“…The median overall survival was significantly longer for PETresponders than for PET-non-responders [hazard ratio (HR): 2.13; 95% confidence interval (CI): 1.14-3.99; P=0.015] (14). A large retrospective single institution study of 301 patients observed a relationship between SUVmax reduction and pathological response (17). As pathologic response was defined by the Mandard tumor regression grades (TRGs) 1-3 (19), SUV changes could identify pathologic response [odds ratio (OR) for each percentage reduction: 1.03; 95% CI: 1.01-1.06; P=0.003] (17).…”
Section: Predicting Preoperative Chemotherapy Response By Pet-ctmentioning
confidence: 99%
“…Using SUV mean , the TGV mean was calculated, whilst using the SUV max the TGV max was produced. All these metrics can be calculated as baseline values or, ideally, as a composite metric such as ΔMTV, ΔTGV max and ΔTGV mean (7). Combination of spatial data with metabolic response resulted in improved prediction.…”
mentioning
confidence: 99%